MAN-COMPUTER GESTALT AND THE NOOSPHERE THEORY: WILL THE COMPUTER BE HUMANIZED OR THE MAN COMPUTERIZED? - Ercegovac, Ivana; Milivojević, Tatjana; Manić, Ljiljana (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2025)
Abstract: For the last several decades, internet has penetrated so deep in our everyday life and became the very essence of our being as well as of the way we function, so the question arises whether the internet has become an integral part of our life, or its users are just the factors of the global network system. Many scientists are trying to answer the question whether the moment of the internet taking over the role of the global consciousness is close. Artificial intelligence is used in more aspects each day of our lives, and the present testifies just how much people rely on the symbiosis with elements of technology with one foot in the virtual world. There are several directions of reflection regarding the future of interaction or symbiosis between man and machines. This paper deals with these concepts, gives the review of theories addressing the same issue and tries to explain the idea why the total control of the machine over the humankind is basically – not plausible.